The Incidence of the EFL Methodology to foster Intensive Basic English Students’ four Macro Skills at the Western Multidisciplinary Campus in the Year 2006 - Calderón Lima, Betsy E.; Escobar Ramírez, Vanessa L.; Mendoza Ruedas, Armando A.; Peraza Mira, Miguel Ángel (2024)
The goal of this study was to determine the most suitable methodological procedures approaches, methods, techniques, and EFL theories in teaching Basic English at the Western Multidisciplinary Campus. The assumption that led to this research study was that the EFL methodology applied in the Intensive Basic English Courses hinders the development of the language skills. To collect the information, the researchers administered a semi-structured interview to fifteen English teachers in the field of EFL methodology in order to answer the questions: What are the most suitable EFL methodological procedures to balance the development of the language skills in basic English students? and in what manner do appropriate methodological procedures help basic English students to develop the four macro skills equally and naturally?. Through a meticulous analysis and interpretation of the data, the researchers found out that according to the EFL teachers in the field of methodology one of the most useful methods to develop the language skills is the Direct Method. Also, they agreed that the most useful activities to foster the language skills are the ones related to authentic materials.